Functional analysis of atfA gene to stress response in pathogenic thermal dimorphic fungus penicillium marneffei - Nimmanee,P. (Public Library of Science, 2015)
© 2014 Nimmanee et al. Penicillium marneffei, the pathogenic thermal dimorphic fungus is a causative agent of a fatal systemic disease, penicilliosis marneffei, in immunocompromised patients especially HIV patients. For growth and survival, this fungus has to adapt to environmental stresses outside and inside host cells and this adaptation requires stress signaling pathways and regulation of gene expression under various kinds of stresses. In this report, P. marneffei activating transcription factor (atfA) gene encoding bZip-type transcription factor was characterized. To determine functions of this gene, atfA isogenic mutant strain was constructed using the modified split marker recombination method. The phenotypes and susceptibility to varieties of stresses including osmotic, oxidative, heat, UV, cell wall and cell membrane stresses of the mutant strain were compared with the wild type and the atfA complemented strains. Results demonstrated that the mRNA expression level of P. marneffei atfA gene increased under heat stress at 42°C. The atfA mutant was more sensitive to sodium dodecyl sulphate, amphotericin B and tert-butyl hydroperoxide than the wild type and complemented strains but not hydrogen peroxide, menadione, NaCl, sorbitol, calcofluor white, itraconazole, UV stresses and heat stress at 39°C. In addition, recovery of atfA mutant conidia after mouse and human macrophage infections was significantly decreased compared to those of wild type and complemented strains. These results indicated that the atfA gene was required by P. marneffei under specific stress conditions and might be necessary for fighting against host immune cells during the initiation of infection.